The status of taxa of suhgenus Aedes (Diptera, Culicidae, Aedes) esoensis Yamada, rossicus Dotheskin, Gorickaja &Mitrofanova, cinereas Melgen, geminus Peus. 1. Overview. Issue 16 (2003) - Gomostacva, Rimma M.
No abstract available